2020
DOI: 10.1007/s13204-020-01444-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZnO nanoparticle ratio and size on mechanical properties and whiteness of White Portland Cement

Abstract: The impact of nanotechnology on the cement industry has been extensively studied. Much work remains needed to improve product quality, decrease cost, and minimize the negative environmental impact. The present study explores the influence of ZnO nanoparticles on physical, chemical, and mechanical properties of White Portland Cement (WPC). Zinc oxide nanoparticles were prepared by simple ball-milling to reach average particle sizes of 70, 37, 27, and 24 nm. For each of the four size groups, ZnO nanoparticles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Similarly, Shafeek et al (2020) showed that the initial setting and final setting were delayed by 38 h and 55 h, respectively, when 1 wt.-% of ZnO nanoparticles was incorporated into the cement. Like our study, other researchers confirmed that higher dosages of ZnO nanoparticles can contribute to the decrement of composites' strength (Thangapandi et al 2020).…”
Section: Consistency and Compressive Strength Of Mortarsmentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, Shafeek et al (2020) showed that the initial setting and final setting were delayed by 38 h and 55 h, respectively, when 1 wt.-% of ZnO nanoparticles was incorporated into the cement. Like our study, other researchers confirmed that higher dosages of ZnO nanoparticles can contribute to the decrement of composites' strength (Thangapandi et al 2020).…”
Section: Consistency and Compressive Strength Of Mortarsmentioning
confidence: 89%
“…Thus, the strength development in the first weeks of hydration is impeded. However, at later testing ages, specimens exhibit satisfactory mechanical performance (Shafeek et al 2020). The calorimetric study held by Siler et al (2019) showed that in OPC system, induction period length increased from 3.3 to 97.4 h when 1 wt.-% of ZnO nanoparticles was incorporated into the cementitious system.…”
Section: Consistency and Compressive Strength Of Mortarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of zinc on mechanical properties is not studied in this study. According to the available literature, it can be assumed that zinc reduces strength in the first days of hydration due to slowing hydration, but long-term strength may increase due to a different hydration mechanism and also, the possibility of zinc compounds acting as microfiller [ 40 ]. In the case of a combination with fly ash, long-term strengths may also increase due to a chemical (e.g., pozzolanic reaction) and physical effect (e.g., microfiller) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Many studies suggested that zinc incorporation also could enhance bone repair. 15,16 Zinc has the ability to boost the expression of genes, including OPG (osteoprotegerin) and RANKL (receptor activator of nuclear factor-k B ligand) in the process of co-culturing with osteoblast. 17 We can deduce that Sr and Zn have a synergistic effect in promoting the formation of bone and inhibiting bone resorption aer introducing Sr and Zn into CPP (calcium polyphosphate).…”
Section: Introductionmentioning
confidence: 99%